Effect of Acid Activation and Al Impregnation in Preparation of Bleaching Earth Catalyst for Glyerol Ketalization - Tarmidzi, Fadhil Muhammad; Sa'pangan, Desly Angeline; Adawiyah, Winda Robiatul; Gunawan, Adrian (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Indonesia's increased biodiesel production represents the government's support for implementing replacement strategy of diesel to biodiesel (B30). The consequence's includes a higher production of glycerol as a byproduct. Currently, glycerol's use in Indonesia has remained limited to the pharmaceutical, polymer, and agricultural industries. On the other side, another application for glycerol as a biodiesel additive is being explored. Therefore, glycerol must be valorized in order to promote the development of clean bioenergy in Indonesia. Solketal as biodiesel additive can be produced by ketalizing glycerol with acetone in the presence of catalyst under acidic condition. In this research, a bleaching earth catalyst, one of the components utilized as a bleaching agent in the biodiesel industries, was developed. Bleaching earth is a form of clay with acidic characteristics that makes it an excellent catalyst in the ketalization process. To increase its surface area and active side, it was activated with sulfuric acid and impregnated with aluminum. The XRD and SEM analyses revealed no significant changes in the catalyst, however the IR spectra revealed a drop in the intensity of the Al-O group. The ketalization process was carried out at 60oC for 2 hours with a catalyst load of 1.5% and a glycerol:acetone:ethanol ratio of 1:1:1. The activation process with 15 M sulfuric acid and 1:1 impregnation was able to convert 15.22% glycerol while 1:5 impregnation is 23.73%. In this study, the catalyst load variation was also carried out which also increased the conversion to 60.53% with 5% catalyst load. Based on these results, it shows that the activation process has more effect on glycerol conversion compared to the impregnation process. In addition, the catalyst load in ketalization is also able to increase the conversion of glycerol.